Public Expenditure Tracking Survey : Afghanistan - Education Sector, Synthesis Report - World Bank (Washington, DC, 2013)
The Public Expenditure Tracking Survey (PETS) looked at four components essential to the strengthening and development of the education sector in Afghanistan: 1) the payment of staff salaries; 2) the availability and use of an operations and maintenance (O&M) budget to support administrative teams and schools; 3) the construction of new schools through the Education Quality Improvement Program (EQUIP); and 4) the distribution of textbooks. The overall objective of the PETS is to understand the dynamics of resource flows in the education sector, to articulate a number of recommendations to improve effectiveness of this resource flow and increase the impact of reforms in the education sector in Afghanistan. This first study will focus on key aspects of resource flow: the extent to which public resources reach service-delivery points (schools); the timeliness of that delivery; the type and scale of bottlenecks and anomalies in the system that may result in delay or leakage of inputs to services; the capacity and flexibility available amongst local officials at all levels to address these bottlenecks. The report is organized as follows: section two presents an overview of the financial landscape of education in the country as well as specific profiles of the three provinces and districts where the research was carried out. Section three looks at the issues related to the payment of salaries and wages to teachers. Section four presents the factors that lead to inefficiencies in meeting the O&M needs of schools and provincial offices. Section five presents the state of completion of schools under EQUIPs and analyses the reasons that lead to these in the three provinces. Section six tracks the distribution of textbooks to provinces from the central level to the schools.